System-Level Quality Improvement Initiatives: Lessons from Keystone and Other Large-Scale Projects - Hyzy, Robert; Posa, Pat; Scales, Damon C. (Seminars in Respiratory and Critical Care Medicine, 2012)
Health care systems around the world are seeking system-level interventions to improve the quality and safety of care because of increasing awareness that many patients do not receive recommended therapies or suffer preventable complications. This has also been motivated by a drive to deliver health care more cost-effectively, and to be more accountable to payers and other stakeholders. The Keystone Project in Michigan is one example of a large-scale system-level initiative that successfully changed the “culture of safety” in the intensive care units of participating hospitals and led to improvements in both process outcomes and clinical outcomes. This article discusses factors that contributed to the success of the Keystone Project and also considers its economic implications. There are also recommendations for the design and evaluation of future system-level quality improvement programs.
Keywords: quality improvement; cost-effectiveness; patient safety; critical care; intensive care units; health economics